Editorial: Photography, artists and museums - Stylianou-Lambert, Theopisti; Stylianou, Elena (My University, 2014)
This special issue of Photographies is dedicated to the intricate relationship between photography and museums. More specifically, it focuses on artistic practices that use photography to challenge the theoretical complexities of this relationship. The featured papers of this issue examine what happens when artists turn their lens on such museum practices as collecting, archiving, exhibiting and interpreting
Keywords: Photography; Museum; Visually communicate